Regional Peak Mucosal Cooling Predicts Radiofrequency Treatment Outcomes of Nasal Valve Obstruction. (3rd November 2020) - Wu, Zhenxing; Krebs, Jillian P.; Spector, Barak M.; Otto, Bradley A.; Zhao, Kai; Farag, Alexander A.
Abstract : Objectives/Hypothesis: Low energy radiofrequency may offer effective treatment for narrow or obstructed nasal valve, yet its precise mechanism is not fully understood. Study Design: Prospective, nonrandomized, case series. Methods: Twenty prospective patients with internal nasal valve obstruction underwent office‐based Vivaer treatment (Aerin Medical, Inc) under local anesthesia. Computational fluid dynamics (CFD) models were constructed based on the pre‐ and 90 days post‐procedure computed tomography (CT) scans to identify salient changes in nasal airflow parameters. Results: Patients' Nasal Obstruction Symptom Evaluation score (NOSE: pre‐treatment 78.89 ± 11.57; post‐treatment 31.39 ± 18.30, P = 5e‐7) and Visual Analog Scale of nasal obstruction (VAS: pre‐treatment 6.01 ± 1.83; post‐treatment 3.44 ± 2.11, P = 1e‐4) improved significantly at 90 days after the minimally invasive approach. Nasal airway volume in the treatment area increased ~7% 90 days post‐treatment (pre‐treatment 5.97 ± 1.20, post‐treatment 6.38 ± 1.50 cm 3, P = .018), yet there were no statistically significant changes in the measured peak nasal inspiratory flowrate (PNIF, pre‐treatment: 60.16 ± 34.49; post‐treatment: 72.38 ± 43.66 ml/s; P = .13) and CFD computed nasal resistance (pre‐treatment: 0.096 ± 0.065; post‐treatment: 0.075 ± 0.026 Pa/(ml/s); P = .063). As validation, PNIF correlated significantly with nasal resistance (r = 0.47, P = .004). Among all the variables, only the peak mucosal cooling posterior to the nasal vestibule significantly correlated with the NOSE at baseline (r = −0.531, P = .023) and with post‐treatment improvement (r = 0.659, P = .003). Conclusion: Minimal remodeling of the nasal valve (7% in this study) may have a profound effect on perceived nasal obstruction, despite little effect on nasal resistance, or PNIF. The results corroborated our previous findings that subjective relief of nasal obstruction correlates with regional mucosal cooling rather than nasal resistance or peak flow rate, a potential target for future effective, personalized therapeutic approaches. Level of Evidence: 4 Laryngoscope, 131:E1760–E1769, 2021